The Prevalence and Associated Factors of Iron Deficiency Anemia among Female in Mahasawat subdistrict, Nonthaburi - Rasmeehirun, Pakpoom (Journal of Nursing, Siam University, 2021)
Iron deficiency anemia is one of the public health problem in Thailand. Anemia may be associated with increased mortality and length of hospital stay. This study aimed to investigate prevalence and associated factor to iron deficiency anemia among women in Mahasawat subdistrict, Bang-kruai district, Nonthaburi. A cross-sectional study was conducted in 167 women(aged older than 18 years). The data were analyzed by using descriptive statistics ,Chi-square’s test, Fisher’s exact test and multiple regression for calculating the prevalence and testing the relationship between iron deficiency anemia and associated factor. Results The prevalence of iron deficiency anemia among women was 10.78%. Those were likely to be majority in women who had the age younger than 60 years, the income more than 100,000 baht/year, education lower than bachelor’s degree, diabetes mellitus, essential hypertension, dyslipidemia, Aspirin/NSIAD usage, menstruation, working people, non-smoker, non-alcoholic drink, Marriage,and BMI between 23-29.99 kg/m2 . The related factor of iron deficiency anemia were NSAIDs/Aspirin. Empirical iron supplement without conducting a serum ferritin test can calculate number needed to treat of 2.39 and save budget 62.3-73.5 %. Conclusion: The prevalence of iron deficiency anemia among women was 10.78%. The prevalence was lower than Thailand prevalence, Characteristics of the study population add more variability to IDA prevalence. Elevated ferritin levels may be associated with other conditions. Other laboratory tests that may be used in the diagnosis of IDA are as follows: Serum iron, Total Iron Binding Capacity (TIBC) and transferrin saturation